1996
DOI: 10.1097/00007890-199606150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Prostaglandin E1 Concentrations and Hemodynamics During Intravenous Infusions of Prostaglandin E1 in Humans and Swine1

Abstract: Prostaglandin (PG) E1 administered intravenously has been used for the treatment of primary nonfunction of hepatic allografts and fulminant hepatic failure. It has been proposed that this therapy may improve hepatic blood flow via the vasodilating properties of PGE1. However, PGE1 undergoes extensive metabolic inactivation by the lung and the concentration of PGE1 reaching the liver during intravenous administration has not been determined. Thus, we measured plasma PGE1 concentrations in patients with hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Quantification of PGE 2 and PGF 2 -PGE 2 and PGF 2 were measured with a stable isotope dilution gas chromatographic/ negative ion chemical ionization/mass spectrometric (GC/ NICI/MS) assay (38). Briefly, PGE 2 -d 4 (2.12 ng) and PGF 2 -d 4 (0.84 ng) internal standards were added to the media samples.…”
Section: Secretion Of Il-6 and Il-8 Via Multiplexmentioning
confidence: 99%
“…Quantification of PGE 2 and PGF 2 -PGE 2 and PGF 2 were measured with a stable isotope dilution gas chromatographic/ negative ion chemical ionization/mass spectrometric (GC/ NICI/MS) assay (38). Briefly, PGE 2 -d 4 (2.12 ng) and PGF 2 -d 4 (0.84 ng) internal standards were added to the media samples.…”
Section: Secretion Of Il-6 and Il-8 Via Multiplexmentioning
confidence: 99%
“…The PVF increase in the SMA group was caused by an increased SMA flow, whereas PGE 1 concentration in systemic circulation became too low to influence SMA flow in the IV and PV groups. This is attributable to high inactivation rates of PGE 1 in the lungs (23) and livers (24). Moreover, an increase in PVF in the SMA group produced an increase in the oxygen content of portal blood.…”
Section: Survival Rate Of Animals and Histologic Examination Resultsmentioning
confidence: 99%
“…On the other hand, a recent report by Awad et al [6]demonstrated that current clinical protocols for intravenous administration of PGE 1 did not raise plasma concentrations of PGE 1 sufficiently and were not likely to affect perihepatic hemodynamics at such a dosage. From our results, at a rate of 0.1 µg/kg/min in pigs, hepatic arterial flow increased markedly when given intra-arterially, while it increased slightly when given intravenously.…”
Section: Discussionmentioning
confidence: 98%
“…In treating such severe liver damage, prostaglandin E 1 (PGE 1 ) has attracted attention for its various kinds of protective effects [3, 4]. However, it is known that approximately 70% of PGE 1 is inactivated during a single passage through the lung [5, 6]. Therefore, direct infusion of this drug into the bloodstream in the liver might be more beneficial than systemic intravenous infusion.…”
Section: Introductionmentioning
confidence: 99%